Composite Drilling Monitoring System - Ruddin, Putri Annur Khaleeda Amer (Universiti Sains Malaysia, 2019)
This research presents a monitoring system for composite drilling that inspect the condition of the drill bit using a digital microscope camera with a computer system that implies image processing method for flank wear detection. This project aims to provide a new system by introducing a new camera view angle that can detect wear or changes in the drill bit geometry specifically, flank region in order to determine the tool life span. Images of wear drill bit are captured and later on analyse using MATLAB software to measure wear percentage. The camera view angle is determined based on the principle of illumination and decided to be at 45 degree view angle. Then, the images taken undergo image pre-processing and further analyse to detect wear by image fusion method. During the image pre-processing, the true colour image is converted into binary images and canny edge detector is applied to detect the flank boundary. Morphological operators such as dilation, flood fill, closing, and erosion is then applied to reconstruct the flank region to make sure it is approximately the same shape as the actual flank region. Finally, the reference image and the wear drill bit image are fuse together using Principle Component Analysis (PCA) method and the wear percentage is calculated. This project is divided into two parts which are hardware and software part. For the hardware part, a setup is design and innovated meanwhile for the software part, a MATLAB code is developed to process the images taken and calculate the wear percentage. The algorithm used is referred by Math Work and being adapted into this project to satisfy the objective of this project. At the end of the project, we could observe the changes in the flank wear area as compared to a reference image and the wear percentage can be calculated.